Growth and Yield of Bestari Rice Varieties, Weeds Identification In Various Jajar Legowo Planting System and Fertilization - Budi Rahayu Rena Ningsih; Oktavia Sarhesti Padmini; Siwi Hardiastuti (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2016)
The aim of this research was to determine the interactions between jajar legowo planting system and variations of fertilization on the growth and yield of bestari rice varieties. The research was conducted in Sentono, Karangdowo District, Klaten regency, Central Java. Research started in April to August 2016. The study uses factorial design with two factors. The first factor was the variation of fertilization that consists of three levels, namely: P1 was the dosage recommendation in the form of chemical fertilizer application which was Phonska 600 kg / ha, P2 = 50% chemical fertilizer dosage recommendation plus 10 ton / ha of BATAN’s organic fertilizer products; P3 = 50% chemical fertilizer dosage recommendation plus 10 ton / ha of organic compost product of the Faculty of Agriculture UPN